Land-use elements and attributed ecosystem services: an archetype approach to land-use evaluation at the German North Sea coast - Karrasch, Leena; Klenke, Thomas; Kleyer, Michael (Ecology and society, 2019)
The ecosystem services concept has been introduced as a decisive approach to include ecosystem functioning in land-use planning and stakeholder-driven sustainable development. Early integration of stakeholders in participatory processes in the nexus of ecosystem services, climate adaption, and land-use management is still a demanding challenge. This investigation followed a cognitive approach to archetype analysis. We defined cognitive archetypes as recurrent patterns in individual perceptions of social-ecological relations. Our aim was to identify cognitive archetypes based on stakeholders' perceived relation between land-use elements and ecosystem services as exemplified in a German North Sea coastal region. Land-use elements were spatially explicit and delivered a variety of different ecosystem services. The stakeholders were regional decision makers and experts who represented key societal sectors, i.e., water management, agriculture, nature conservation, regional policy, and tourism. Within a participatory process, these stakeholders individually evaluated a matrix of 19 land-use elements and 18 ecosystem services. In terms of archetype analysis, the stakeholders were considered as different cases, and the evaluation of relationships between land-use elements and ecosystem services built the attributions to identify archetypes. They independently agreed on the relevance of close to one-third of 342 attributions, whereas there was disagreement on approximately two-thirds of the possible attributions. By identifying agreements across different sectors, 2 archetypes in land-use element–ecosystem service attributions were identified. The first archetype built on monofunctional attributions, i.e., one land-use element was relevant for the provision of one ecosystem service. The second archetype described land-use elements attributed to bundles of ecosystem services, indicating multifunctionality of land-use elements. Disagreement can result primarily from sector or individual viewpoints. In the case of disagreements, land-use–ecosystem relationships can reveal archetypical mutually exclusive interests, the third archetype. We found that disagreements were mainly individual and not sector specific. This indicated that individual knowledge on service outputs of multiple land uses differed strongly among the stakeholders, particularly with respect to regulatory services.